Science classroom practices in an Islamic religious secondary school: adapting classroom ethnography - Amnah Abdullah; Mohd. Zaki Ishak; Robert Francis Peters (Global Academic Excellence, 2020)
This article is a response to the article “Classroom Ethnography: Adapt or Adopt?” The aim of this article is to guide potential local postgraduates on the coding process for the selected classroom ethnography which is not well understood. Qualitative data collection and data analysis were used from a larger ethnographic study. We explored in-depth the influence that culture has on learning science in an Islamic Religious Secondary School form five science classroom. The ethnographic fieldwork capturing the informants’ beliefs and values central to their distinctive way of life could provide emerging data for understanding the culture sharing group’s learning of science in a period of time. The choice of manual coding attempts to describe the nature of science classroom practices at this Islamic Religious Secondary School science classroom. This article presents findings that adapting classroom ethnography is possible. We found that the students’ initial sources of cultural influence are the nature of science classroom practices.